2022
DOI: 10.1002/slct.202201040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Core‐Shell Bottlebrush Polymers via Controllable Polymerization

Abstract: This research was focused on the synthesis of well-defined bottlebrush polymers (BBPs) comprising of polynorbornene (PNB) backbones and side-chains of the polylactide (PLA)-bpolystyrene (PS). The PNB backbones were synthesized via ringopening metathesis polymerization of norbornene, and then Llactide (LA) was first grafted to the backbones to form PLA side-chains by ring-opening polymerization. Afterwards, styrene was further grafted to the PLA cantilever with triothiocarbonate modification via reversible addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Core–shell bottle-brush copolymers with diblock side chains have emerged as a focal point in the study of polymer aggregates. These copolymers can generate well-defined individual nanoparticles such as spherical and cylinder micelles, worm-like micelles, , and monolayer and multilayer vesicles . Additionally, it has been demonstrated that these copolymers can assemble strung micelles with increased backbone rigidity. Our previous study revealed that stable single or strung micelles could be obtained separately by adjusting the architectural parameters of core–shell bottle-brush copolymers . Although it is commonly assumed that aggregates formed by core–shell bottle-brush copolymers can exhibit higher stability based on their topology, , the possible transformations between different structures during the flow-driven translocation and the corresponding stability remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Core–shell bottle-brush copolymers with diblock side chains have emerged as a focal point in the study of polymer aggregates. These copolymers can generate well-defined individual nanoparticles such as spherical and cylinder micelles, worm-like micelles, , and monolayer and multilayer vesicles . Additionally, it has been demonstrated that these copolymers can assemble strung micelles with increased backbone rigidity. Our previous study revealed that stable single or strung micelles could be obtained separately by adjusting the architectural parameters of core–shell bottle-brush copolymers . Although it is commonly assumed that aggregates formed by core–shell bottle-brush copolymers can exhibit higher stability based on their topology, , the possible transformations between different structures during the flow-driven translocation and the corresponding stability remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this structure, bottlebrush polymers represent a category of macromolecules with a high density of polymeric side chains. There are several architectures of bottlebrush polymers such as homografted, 13 heterografted, 14 core−shell, 15 or brush-onbrush. 16 In this study, we produced multicompartment nanoto microparticles using core−shell bottlebrush polymers as building blocks.…”
mentioning
confidence: 99%